Heavy Metal Biosorption Characteristics of the Submerged Aquatic Plant (Nasturtium officinale) - OKUMUS*, V.; BASARAN†, D.; ONAY†, A. (Asian Journal of Chemistry, 2009)
In the present investigation an aquatic plant, Nasturtium officinalewas examined for its biosorption ability of heavy metal ions. The resultsobtained from biosorption experiments were used to understand thedriving forces that govern the interaction between metal ions andbiosorbent. The experimental biosorption data were fitted to theScatchard plot, Langmiur and Freundlich isotherms. According to theparameters of the Langmiur isotherm, the maximum biosorption capacitiesof Cd2+ and Co2+ were 0.56 and 0.49 mg/g, respectively. In viewof Freundlich isotherms, the maximum biosorption capacities of Cd2+and Co2+ were 2.23 mg/g for both of metal ions.